Removal of selected organic pollutants in landfill leachate using natural coagulant from dillenia indica seed extract / Aziz Ahmed - Aziz , Ahmed (2021)
This study is aimed to identify and characterise novel green coagulant from Dillenia indica seed extracts for the removal of selected persistent organic pollutants (POPs) in landfill leachate using coagulation-flocculation process. The removal efficacy of D. indica seed extracts was compared with commercially available coagulants namely Locust Bean Gum (LBG) and alum. Additionally, it focused on the optimisation of the variables of the coagulation-flocculation process such as coagulants dosage, pH and mixing speed for POPs removal. The functional groups, morphological behaviour and surface area of the dried flocs and samples were analysed using Fourier transform infrared (FTIR), Scanning Electron Microscopy (SEM), and Brunauer, Emmett and Teller (BET). POPs found in the leachate were phenol, 4,4'-(1-methylethylidene)bis- (Bisphenol A), bis(2-ethylhexyl) phthalate (DEHP), 2,4-Di-tert-butylphenol, Pyridine,3-(1-methyl-2-pyrrolidinyl)-,(S)- (nicotine) and p-tert-Butylphenol (P-t-BP). The seed extracts of D. indica contained active coagulating agents such as carbohydrate 19.47%, proteins 12.78%, phytic acid 6.98% and total phenolics 8.23%. At optimal conditions, D. indica seed extracts removed 66% Bisphenol A, 59% DEHP, 83% 2,4-Di-tert-butylphenol, 80% nicotine, 74% P-t-BP at pH 8.5. From SEM images of floc with D. indica seed extract fibrous netlike structures were observed. FTIR studies showed that D. indica seed contains hydroxyl, carboxyl, and amino groups, as well as, hydrogen bonds. Similarly, LBG effectively removed 100% nicotine, and 96% P-t-BP, 76% Bisphenol A, 69% DEHP and 84% 2,4-Di-tert-butylphenol at pH 4 and pH 6.5, respectively. Floc from treatment of leachate with LBG had identical peaks with LBG powder, but some variation in the peaks of the functional groups, which signifies the chemical interactions between flocculants and pollutant particles resulting in removal of selected POPs. SEM micrographs of floc from treatment of leachate with LBG had a rough cloudy surface and numerous macro-pores compared with alum, which enabled the capture and removal of selected POPs from leachate. The specific surface area of the LBG and D. indica seed were 0.7165 m²/g and 1.6734 m²/g, respectively. Coagulant dosage and pH variation had a significant effect on selected POPs removal in leachate. The sludge volume index (SVI) value of LBG, D. indica seed extracts and alum were 60 mL/g, 52 mL/g and 180 mL/g, respectively, at optimum condition. From the economic point of view, one million litres of leachate using D. indica seed extract (at 1000 mg/L dosage) would cost 0.6 USD while LBG (at 500 mg/L dosage) would cost 0.4 USD and alum (at 1.5 g/L dosage) would cost 3.6 USD. Because of the large surface area, effective pollutants removal efficiency and non-toxicity, D. indica and LBG can be strongly recommended as alternatives to inorganic coagulants for the treatment of POPs in landfill leachate.